Morphological and molecular evidence of some Minuartia species (Caryophyllaceae) from Turkey, with a desciption of a new species - Koç, Murat; Hamzaoğlu, Ergin; Aksoy, Ahmet (Phytotaxa, 2019)
The genus Minuartia is represented in Turkey by 34 taxa. Some interesting specimens were collected from Antalya province, and examined. These specimens resemble Minuartia meyeri, and M. multinervis from which differ by characters (macro-, and micromorphological) of inflorescence, alar pedicels, petals, sepals, capsules and seeds. Moreover, by using the DNA sequences of the ITS genes, phylogenetic relationships between this collected species, and the related species were investigated. As a result of the evaluation of molecular, and morphological data, we proposed to described the population from Antalya as a new species for the science. A description, pictures, distribution, habitat, and IUCN category are given.